First factor (x square -36), the answer will be (x+6)(x-6).
Second, cancel the x .
6x/ (x+6)(x-6)
4x/(6)(-6)
4x/-36
3x-4=5x-10
Subtract 3x from both sides
-4=2x-10
Add 10 to both sides
6= 2x
X= 3
3 times 3-4
AB=5
For this case we must solve the following equation:
![12y + 6 = 6 (y + 1)](https://tex.z-dn.net/?f=12y%20%2B%206%20%3D%206%20%28y%20%2B%201%29)
We apply distributive property on the right side of the equation:
![12y + 6 = 6y + 6](https://tex.z-dn.net/?f=12y%20%2B%206%20%3D%206y%20%2B%206)
We subtract 6y on both sides of the equation:
![12y-6y + 6 = 6\\6y + 6 = 6](https://tex.z-dn.net/?f=12y-6y%20%2B%206%20%3D%206%5C%5C6y%20%2B%206%20%3D%206)
We subtract 6 from both sides of the equation:
![6y = 6-6\\6y = 0](https://tex.z-dn.net/?f=6y%20%3D%206-6%5C%5C6y%20%3D%200)
Dividing by 6 on both sides of the equation:
![y = 0](https://tex.z-dn.net/?f=y%20%3D%200)
So, the result is ![y = 0](https://tex.z-dn.net/?f=y%20%3D%200)
Answer:
![y = 0](https://tex.z-dn.net/?f=y%20%3D%200)
Answer:
1 solution
Key:
Assume <em>x</em> is the the range x > 0 ≥ 1, in other words, assume <em>x</em> is equal to 1.
Step-by-step explanation:
![y = -x - 8x - 16\\= -x - 8x\\= 9x\\= 9x - 16](https://tex.z-dn.net/?f=y%20%3D%20-x%20-%208x%20-%2016%5C%5C%3D%20-x%20-%208x%5C%5C%3D%209x%5C%5C%3D%209x%20-%2016)
Dilation and rotations are similar because they both have to move and both have one mane shop as starting point.